CDK1 couples proliferation with protein synthesis - Hörth, Katharina; Schott, Johanna; Lindner, Doris; Kruse Hollensen, Anne; Kroun Damgaard, Christian; Mongis, Cyril; Knop, Michael; Palm, Wilhelm; Ruggieri, Alessia; Stoecklin, Georg (The journal of cell biology, 2020)
Cell proliferation exerts a high demand on protein synthesis, yet the mechanisms coupling the two processes are not fully understood. A kinase and phosphatase screen for activators of translation, based on the formation of stress granules in human cells, revealed cell cycle-associated kinases as major candidates. CDK1 was identified as a positive regulator of global translation, and cell synchronization experiments showed that this is an extramitotic function of CDK1. Different pathways including eIF2α, 4EBP, and S6K1 signaling contribute to controlling global translation downstream of CDK1. Moreover, Ribo-Seq analysis uncovered that CDK1 exerts a particularly strong effect on the translation of 5′TOP mRNAs, which includes mRNAs encoding ribosomal proteins and several translation factors. This effect requires the 5′TOP mRNA-binding protein LARP1, concurrent to our finding that LARP1 phosphorylation is strongly dependent on CDK1. Thus, CDK1 provides a direct means to couple cell proliferation with biosynthesis of the translation machinery and the rate of protein synthesis.
Gesehen am 17.12.2020